Preliminary findings on the impact of Learn-Before Lecture (LBL) in improves students learning for fundamental physics among Pre-University student - Siti Nazirah Butai; Johannah Jamalul Kiram; Huzaikha Awang; Megawati Mohd Yunus; Azlinah Matawali (Springer Cham, 2025)
Classical mechanics is a challenging physics subject often leading to misconceptions. Traditional teaching methods may offer insufficient lecture time for in-depth understanding and analysis. This study develops and assesses the effectiveness of the Learn-Before-Lecture (LBL) approach among pre-university physics students at Universiti Malaysia Sabah. The objectives are to evaluate academic performance and student perceptions following the LBL interventions, specifically on the topic of elasticity. A mixed-method comparative study involving experimental and control groups was conducted. Results indicated a significant improvement from pre-test to post-test scores in the LBL group; however, no significant difference was found between experimental and control groups' post-test scores. Correlation analyses revealed positive significant relationships among motivation factors (Extrinsic Goal Orientation, Task Value, and Performance) and learning strategies (Elaboration, Critical Thinking, and Metacognitive Self-Regulation). Qualitative analysis further highlighted that students valued extrinsic goals, critical thinking, and metacognitive skills for enhanced understanding of elasticity. In conclusion, LBL shows potential to enhance students' academic performance and positively influence their learning strategies.